2019
DOI: 10.1021/acsami.9b04871
|View full text |Cite
|
Sign up to set email alerts
|

Design of Self-Healing and Electrically Conductive Silk Fibroin-Based Hydrogels

Abstract: Self-healing and electrically conductive silk fibroin (SF)-based hydrogels were developed based on the dynamic assembly/disassembly nature of supramolecular complexes and the conductive nature of polypyrrole (PPy). The self-healing properties of the hydrogels were achieved through host−guest interactions between β-cyclodextrin and amino acid side chains (tyrosine, tryptophan, phenylalanine, and histidine) on SF. PPy deposition was achieved via in situ polymerization of pyrrole using ammonium persulfate as an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 42 publications
0
50
0
3
Order By: Relevance
“…The classification of self-healing mechanisms is summarized in Table 2 and is presented in Figure 3. [66,67] Acylhydrazone bonds [68,69] Microcapsule [70,71] Host-guest interactions [72][73][74] Boronate-diol complexation [75,76] Hydrogen bond [77][78][79] Diels-Alder click chemistry [80][81][82] Hydrophobic interactions [83,84] Disulfide bonds [85,86] π-π stacking [87,88] Imine bonds (Schiff base) [89,90] Electrostatic (or ionic) interaction is based on the interaction between ions incorporated into the HG matrix ( Figure 3A). By the mutual attraction of oppositely charged ions or ions and polymer chains, the HG structure can be reconstructed, e.g., between two pieces of HG placed on each other [66].…”
Section: Self-healingmentioning
confidence: 99%
“…The classification of self-healing mechanisms is summarized in Table 2 and is presented in Figure 3. [66,67] Acylhydrazone bonds [68,69] Microcapsule [70,71] Host-guest interactions [72][73][74] Boronate-diol complexation [75,76] Hydrogen bond [77][78][79] Diels-Alder click chemistry [80][81][82] Hydrophobic interactions [83,84] Disulfide bonds [85,86] π-π stacking [87,88] Imine bonds (Schiff base) [89,90] Electrostatic (or ionic) interaction is based on the interaction between ions incorporated into the HG matrix ( Figure 3A). By the mutual attraction of oppositely charged ions or ions and polymer chains, the HG structure can be reconstructed, e.g., between two pieces of HG placed on each other [66].…”
Section: Self-healingmentioning
confidence: 99%
“…The formations of polymer architectures with host-guest interaction are summarized in Figure 4 ( Yang et al, 2015 ). Common molecules used to form host-guest interaction include crown ethers ( Xue et al, 2015 ), calixarenes ( Yan et al, 2012 ), cucurbiturils ( Appel et al, 2012 ), pillararenes ( Ogoshi et al, 2016 ), and cyclodextrins (CDs) ( Deng Z. et al, 2018 ; Li Q. et al, 2018 ; Liu L. et al, 2019 ; Wang et al, 2019e ; Wu et al, 2008 ). The authors ( Li Q. et al, 2018 ) used β-cyclodextrin and N-vinylimidazole to achieve hydrogel fibers.…”
Section: Mechanism Of Intrinsic Type Self-healing Hydrogelsmentioning
confidence: 99%
“…Dynamic covalent bonds include imine bond ( Qu et al, 2017 ; Yan et al, 2017 ; Chen H. et al, 2018 ; Chen et al, 2019e ; Khan et al, 2018 ; Wei and Gerecht, 2018 ; Zhang et al, 2018 ; Guo B. et al, 2019 ; Jiang F. et al, 2019 ; Li Q. et al, 2019 ; Qian et al, 2019 ; Wang et al, 2019b ; Wang W. et al, 2019 ; Zhou et al, 2019 ), Diels–Alder (DA) reaction ( Oehlenschlaeger et al, 2014 ), boronate-diol complexation ( Hong et al, 2018 ; Pan et al, 2018 ; Smithmyer et al, 2018 ; Zhi et al, 2018 ; Han et al, 2019 ), acylhydrazone bond ( Yang et al, 2017 ; Shen et al, 2019 ; Sun C. et al, 2019 ), dynamic disulfide bond ( Song L. et al, 2019 ), and dynamic metal oordination ( Shao et al, 2018 ; Chen et al, 2019a ; Qin et al, 2019 ). Physical non-covalent interactions include hydrogen bonding ( Fan et al, 2018 ; Uzumcu et al, 2018 ; Cao et al, 2019 ; Chen et al, 2019c ; Hu et al, 2019 ; Huang et al, 2019 ; Kuddushi et al, 2019 ; Li R. et al, 2019 ; Liao et al, 2019 ; Su et al, 2019 ; Wang L. et al, 2019 ), hydrophobic interaction ( Liu P. et al, 2019 ), host-guest interaction ( Deng Z. et al, 2018 ; Li Q. et al, 2018 ; Liu L. et al, 2019 ; Wang W. et al, 2019 ), and ionic interaction ( Ma et al, 2018 ; Wang Y. et al, 2018 ; Becher et al, 2019 ). Some intrinsic type self-healing hydrogels even have several kinds of networks, containing either one type or several types of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al 11 found that the conductivity of SF-PPY film was about 1.1 S/cm. Liu et al 12 showed that the PPY-coated SF-β-cyclodextrin dual-crosslinked hydrogels prepared via the chemical polymerization method only achieved a conductivity of 0.8 ± 0.2 S/cm. It was demonstrated that the PC12 cells displayed better adhesion and spreading on the substrates with higher conductivity.…”
Section: Introductionmentioning
confidence: 99%